Pengembangan Media Pembelajaran Berbantuan Adobe Animate melalui Pendekatan Realistic Mathematic Education pada Materi PLSV - Nushrotin Niswah; Nanang Nabhar Fakhri Auliya (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
In mathematics, especially in the material of linear equations of one variable, learning media has a very vital role to maximize the success of the learning process. Through realistic mathematics learning methods, it can help students use interactive media to more easily understand complex concepts. The purpose of this research is to explain the steps for creating Adobe Animate-based learning media on PLSV material and to assess how useful it is as a tool in learning activities. Research and development (R&D) applies the 4-D development model (Define, Design, Develop, and Disseminate). The results of the assessment stated that Adobe Animate-based learning media for the PLSV topic is very suitable for use as a supporting tool in learning the subject. Small-scale trials showed a practicality of 93%, while large-scale trials showed a practicality of 95%.